SUICIDAL HANGING WITH FINGERS INTERPOSED BETWEEN NOOSE AND NECK: CHARACTERSTIC INJURIES IN SERIES OF CASES - Balaji, D; Venkatesh, J; Behera, Chittaranjana; Sikary, Asit (Journal of Forensic Medicine and Toxicology, 2024)
A ligature mark is a significant evidence for hanging and strangulation. Based upon the pattern of ligature it can differentiate. The presence of injuries around the neck apart from ligature mark known as peri-ligature injury. It may lead to misperception of injuries directed towards for discontinuity are padding on the neck and scalp or beard hairs. Very rarely, the hands or fingers of the victim could be found entrapped in neck ligature. It could be due to a self-rescue effort by the victim at the last moment in ligature strangulation.3 But in case of hanging to avoid pain and discomfort due to friction of ligature material around the neck.4 During the post mortem examination, finger entangled between noose and neck can present as an unusual position of the hands (maybe fixed due to rigor mortis) and presence of neck injuries apart from the ligature mark known as peri-ligature injuries. Hence, We are reporting three cases of suicidal hanging in which a finger was interposed between the neck and ligature causing peri ligature injuries., which are rarely reported.